2015
DOI: 10.1186/s12862-015-0363-8
|View full text |Cite
|
Sign up to set email alerts
|

Were sea level changes during the Pleistocene in the South Atlantic Coastal Plain a driver of speciation in Petunia (Solanaceae)?

Abstract: BackgroundQuaternary climatic changes led to variations in sea level and these variations played a significant role in the generation of marine terrace deposits in the South Atlantic Coastal Plain. The main consequence of the increase in sea level was local extinction or population displacement, such that coastal species would be found around the new coastline. Our main goal was to investigate the effects of sea level changes on the geographical structure and variability of genetic lineages from a Petunia spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 69 publications
5
42
0
Order By: Relevance
“…Further, Pleistocene climatic changes have also been invoked to explain diversification within BAF (e.g., Cabanne et al., ; Cardoso, Cristiano, Tavares, Schubart, & Heinze, ), by persistence of rainforest species in stable areas (refugia) in the northern bioclimatic region and expansion of open vegetation formation in the south (Carnaval et al., ). These global climatic changes also had impacts on sea level, which in turn might have influenced the geographic distribution of coastal vegetation (Ramos‐Fregonezi et al., ), for instance by the exposition of Brazilian continental shelf during glacial periods (Leite et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, Pleistocene climatic changes have also been invoked to explain diversification within BAF (e.g., Cabanne et al., ; Cardoso, Cristiano, Tavares, Schubart, & Heinze, ), by persistence of rainforest species in stable areas (refugia) in the northern bioclimatic region and expansion of open vegetation formation in the south (Carnaval et al., ). These global climatic changes also had impacts on sea level, which in turn might have influenced the geographic distribution of coastal vegetation (Ramos‐Fregonezi et al., ), for instance by the exposition of Brazilian continental shelf during glacial periods (Leite et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…integrifolia under the latter taxa, justifying this choice with the association of several characteristics to the different environments where these plants grow. Previous evolutionary approaches (Longo et al , 2014; Reck-Kortmann et al , 2014; Ramos-Fregonezi et al , 2015) have supported the suggestions of Stehmann and Bohs (2007) and Stehmann et al (2009), but the genetic variation found in WOX genes reinforces the proposition of Ando et al (2005a,b), this indicating the need for more studies including these different morphologies.…”
Section: Discussionmentioning
confidence: 59%
“…Despite the differences in the intraspecific divergence history between C. heterophylla (Mäder et al, 2013) and the codistributed P. integrifolia subsp. depauperata (Ramos-Fregonezi et al, 2015), both taxa shared the same pattern of high genetic admixture based on microsatellite data in populations located at the east of Patos Lagoon (Silva-Arias et al, 2017). This congruent pattern between species indicates that the current and historical dynamics in the topographical and environmental conditions in SACP are responsible for the admixture patterns and the genetic structure in this region.…”
Section: Patos Lagoon Development Let To a Secondary Contact Between mentioning
confidence: 63%
“…The most substantial transgression and regression cycles let the formation of four main sand barriers to be positioned parallel to the coastline (barrier-lagoon systems I to IV; Tomazelli et al, 2000;Tomazelli and Dillenburg, 2007). The harsh environment, such as strong spring-summer sea breezes from the northeast and high insolation, strongly influences this region such as strong spring-summer sea breezes from the northeast and high insolation (Dillenburg et al, 2009), which was responsible for the current topography and, consequently, influenced the distribution and variability of genetic lineages in contemporary plants (e.g., Mäder et al, 2013;Ramos-Fregonezi et al, 2015;Silva-Arias et al, 2017).…”
Section: Introductionmentioning
confidence: 99%